Production of Cellulases by Indigenous Fungi (Aspergillus SP. and Trichoderma SP.) for Subsequent Use in Bioconversion of Palm Oil Mill Effluent Solid to Sugar - Wong, Kok Mun (2005)
The isolation of fungi was done from sources such as palm oil plantation, rotten fruits and et cetera, where out of fifty colonies isolated, six strains showed positive result on cellulose degradation and only two cellulolytic fungi were selected to undergo optimization. They were identified as Aspergillus sp and Trichoderma sp respectively. In the optimization process, different parameters were studied in order to increase the cellulases activity for both the fungi. Different types of substrates were tested such as POME solid, carboxylmethylcellulose (CMC) and sugarcane bagasse. From the results obtained, sugarcane bagasse was the best substrate to induce the production of cellulases from the fungi. Therefore, in the optimization process sugarcane bagasse was used to examine the effect of different parameters conditions such as temperature, nitrogen source, inoculum size and inoculum age. The fermentation that was carried out at 37°C, mixture of nitrogen sources consisted of (NH4)2SO4, KNO3, peptone and urea, 10% (v/v) inoculum size and at 48 hours of inoculum age proved to be the best conditions for cellulases production. For Aspergillus sp, 0.85 U/mL FPase, 2.03 U/mL CMCase and 3.00 U/mL β-glucosidase were obtained whereas for Trichoderma sp 0.90 U/mL FPase, 3.00 U/mL CMCase and 0.11 U/mL β-glucosidase were recorded respectively. The crude cellulase obtained was precipitated with ammonium sulphate to be further utilized in the saccharification process. The temperature stability and pH profile of the crude enzyme were also examined. The saccharification process for sugar production was carried out in controlled parameters such as different chemical pretreated POME solids, different ratio of enzyme concentration and different pH. The highest reducing sugars and glucose produced by using the crude enzyme were 22.8 g/L and 14.8 g/L respectively. Comparison on sugar production from POME solid by using diluted commercial cellulase enzyme for sugar production from POME solid was also done. About 0.23 g of reducing sugars and 0.15 g of glucose per gram of substrate was yielded by using the crude enzyme in the saccharification process. In conclusion, the objectives of the study were achieved with the isolation of local cellulase-producing fungi.